2022
DOI: 10.1371/journal.pone.0262779
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory response to early rehabilitation in critically ill adults: A secondary analysis of a randomised controlled trial

Abstract: Introduction Early rehabilitation is indicated in critically ill adults to counter functional complications. However, the physiological response to rehabilitation is poorly understood. This study aimed to determine the cardiorespiratory response to rehabilitation and to investigate the effect of explanatory variables on physiological changes during rehabilitation and recovery. Methods In a prospectively planned, secondary analysis of a randomised controlled trial conducted in a tertiary, mixed intensive care… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…An assessment of activities is important as, until now, detailed information on the performed physical activity of IC patients during an ICU stay has been lacking. Furthermore, although IC patients are not highly active, a recent study found significant variations in physiological responses to different types of activities [ 2 ] indicating that an assessment of all types is immensely important. To enhance rehabilitation in IC patients, an appropriate amount of physical activity is essential [ 27 ], and objective measurements about the type, intensity, frequency, and duration of performed activity by IC patients are essential [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of activities is important as, until now, detailed information on the performed physical activity of IC patients during an ICU stay has been lacking. Furthermore, although IC patients are not highly active, a recent study found significant variations in physiological responses to different types of activities [ 2 ] indicating that an assessment of all types is immensely important. To enhance rehabilitation in IC patients, an appropriate amount of physical activity is essential [ 27 ], and objective measurements about the type, intensity, frequency, and duration of performed activity by IC patients are essential [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being physically active as a form of rehabilitation, even in the early stages of recovery, is important for optimizing physical functioning and increasing autonomy [ 1 ]. Therefore, adequate physical activity in the IC setting is important for improving physical functioning [ 2 , 3 ]. However, what constitutes “adequate” physical activity has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The nurses might focus on patient's ventilation or wellbeing and perceive mobilisation to be sitting in a chair together with family even though this is done by hoist and categorised as passive mobilisation (Laerkner et al, 2019). However, there is a difference in the metabolic demands required of the patients which must be taken into account when planning mobilisation to match the capacity and condition of the patents as well as to allow sufficient time for recovery (Eggmann et al, 2022). Furthermore the need of planning and use of assisting devices varies along with a stepwise hierarchy of mobility intensity (Hodgson et al, 2015).This reflects a need for interprofessional communication to align expectations and support continuity whilst at the same time sustaining a situation-specific mobility plan to optimise mobilisation of conscious and mechanically ventilated ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recognising that mobilisation must be regarded situation‐specific, it might at times be beneficial to limit the actions; whereas other times to increase the effort to progress to the next level of physical function. Eggmann et al recommend shorter and more frequent mobilisation sessions to adapt duration, frequency, and intensity to the patients' actual conditions (Eggmann et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation